Analysis of Injuries over Neck and its Association with Ligature Mark in Hanging and Strangulation - Shabbir, Sheeba (International Journal of Pathology, 2020)
Objective: To study gross and microscopic patterns of ligature mark in antemortem and postmortem hanging and strangulation. Materials and Methods: A descriptive study was conducted in Federal Government Services Hospital Islamabad. 106 cases of asphyxia death were analyzed. The victims age, sex, socioeconomic status, site of incident was noted and analyzed by using SPSS 20. These cases were studied in detail by review of history, police papers and postmortem findings etc. Other parameters such as manner of death, ligature mark its level of constriction, number of rounds, position, type of material and internal appearance was also noted. Results: The site and position of ligature is significant in typical cases of hanging and strangulation. Microscopic examination of ligature mark in hanging (n=41) showed discontinuity, breaking, wrinkling and compression of the skin (dermal and epidermal layers) along with micro hemorrhages and inflammatory changes in subcutaneous tissues. Underlying soft tissues beneath the ligature mark on the neck were glistening white in appearance in all cases of hanging while it showed extravasations of blood in all ligature strangulation cases (n=44). Conclusion: It was concluded that the ligature mark needed to be evaluated along with other external features, internal findings and histopathological features. Histopathological examination of the ligature mark gives significant information that can be very helpful in diagnosing deaths due to ligature strangulation or hanging. The correlation of external, internal and microscopic findings may be helpful in diagnosing